Bifurcated hydrogen bonds in platinum(II) complexes with phosphinoamine ligands. (15th September 2019) - Sojka, Martin; Tousek, Jaromir; Badri, Zahra; Foroutan-Nejad, Cina; Necas, Marek
Graphical abstract: Bifurcated intramolecular hydrogen bonding was investigated in Pt(II) complexes. The most prominent NH…ClPt interactions are found in the cis complexes with para substituted phosphinoamine ligands, which show delocalization indexes (DI) up to 0.09. The ortho substituted phosphinoamine ligands decrease the DI values down to zero for C(O)OCH3 and C(O)CH3 moieties. Abstract: In this work we report an investigation of the influence of bifurcated intramolecular hydrogen bonds on conformations of platinum(II) complexes with phosphinoamine ligands. The series of new cis and trans -PtCl2 L2 complexes with phosphinoamine ligands was synthesized and characterized by 1 H, 31 P, 195 Pt NMR, IR, and molecular structures of 8 complexes were determined by X-ray crystallography. The hydrogen bonds are observed between NH⋯ClPt and NH⋯R (R = COOCH3, C(O)CH3, F, CN) moieties of the ligands and Pt core. The structural data from X-ray diffraction are linked to calculated conformational energies from density functional theory (DFT) and topological analysis results obtained from quantum theory of atoms in molecules (QTAIM) calculations. The most prominent NH⋯ClPt interactions are found in the cis complexes with para substituted phosphinoamine ligands, which show delocalization indexes (DI) up to 0.09. The ortho substituted phosphinoamine ligands decrease the DI values down to zero for C(O)OCH3 and C(O)CH3 moieties.